Experimental Study of Thyroid Disturbances and Interplay with Growth Hormone on Body Development and Lipid Profile in Immature Male Rats - Sinan Abdullah (Basrah Journal of Veterinary Research)
Background: The endocrine system is an essential feature of the pituitary gland, which controls various hormonal activities. Disturbances in development-associated thyroid and growth hormones may lead to significant alterations in development of the body weight, length and mass index (BMI), abdomen circumference and tail length, as well as the plasma lipid profile, thus changing of body physiology.Materials and Methods: This research employed fifty immature male rats which were separated into control, GH deficiency (GHD), GH supplementation, hypothyroidism and hyperthyroidism groups. The rats underwent hormonal treatments over 21 days during which time changes in the pituitary gland physiology by developmental and plasma lipid profile changes.Results: Body development Control Group has been growing in length throughout the 10 weeks. The highest length growth was observed with GH Addition and the lowest with GH Deficiency . Hence, the Hypothyroid Group grew substantially less in length compared to the Control. In contrast, the Hyperthyroid Group showed minimal deviation or even paralleled to the Control Group. In lipid profile, in growth hormone deficiency group the average of cholesterol, triglyceride, LDL and VLDL level were decreased, while the average of HDL level were increased. Conclusion: This work reveals more about the important influences of thyroid and growth hormone disruptions on pituitary gland physiology and rat health, highlighting the organ’s flexibility and essential controlling function in childhood.Keywords: Pituitary Gland, Growth Hormone, Lipid profile, Endocrine System, Development, Rats.